Design and performance study on a large-scale hybrid CPV/T system based on unsteady-state thermal model. (1st January 2019) - Wang, Zexin; Wei, Jinjia; Zhang, Gaoming; Xie, Huling; Khalid, Muhammad
Highlights: A large-scale south-north tracking hybrid CPV/T system was constructed. The photo-voltaic and thermal performance of the system were investigated. An unsteady-state thermal model of hybrid CPV/T system was developed. The unsteady model can predict the instantaneous thermal performance accurately. Abstract: A hybrid CPV/T unit designed in this work concentrates solar radiation by a compound parabolic concentrator (CPC) and converts solar energy into electrical and thermal energy by a PV/T module. The CPC eliminating multiple reflections of solar radiation is defined as the 'EMR-CPC' in our previous work, which improves photoelectric and thermal conversion efficiencies. Two similar CPV/T units were tested with two-axis tracking device and south-north single-axis tracking device respectively, and the average photoelectric conversion efficiencies were 13% and 12%. A large-scale south-north tracking hybrid CPV/T system with sunlight collecting area of 810 m 2 was built to explore practical application of this CPV/T unit. The whole-day thermal efficiency and total thermal output of the large-scale hybrid CPV/T system were 55% and 1, 730, 039 kJ respectively on April 14, 2017. The steady-state and unsteady-state thermal models of the hybrid CPV/T system were established and the energy loss was analyzed. The calculated whole-day comprehensive thermal efficiencies of the unsteady-state thermal model and the steady-state thermal model were 55.3% and 55.0% respectively, which were close to the measurement 55.8%. However, the steady-state thermal model failed to accurately predict the whole-day thermal efficiency variation of the system. In comparison, the unsteady-state thermal model accurately predicts instantaneous thermal efficiency of the system varying with meteorological conditions and its total daily heat output.